Performance Comparison of Two Waste Plastics (Low-Density Polyethylene (LDPE) and Polyethylene Terephthalate (PET)) for Asphalt Pavement on the Basis of Marshall Test - Khadka, Reeta; Poudel, Dipika; Timsina, Dikshya; Madai, Padam Bahadur (International Journal on Engineering Technology, 2024)
Plastic disposal is a significant problem as it is non-biodegradable and causes air pollution if burned. The utilization of waste plastics in road construction has gained attention due to environmental concerns and the need for sustainable development of infrastructure. This research investigates the performance analysis of two different waste plastics, lowdensity polyethylene (LDPE) and polyethylene terephthalate (PET), for the construction of asphalt pavement based on the Marshall Stability Test. The Optimum bitumen content (OBC) is found to be 5.2% and LDPE and PET (8% and 10% by weight of bitumen) were used. The use of both LDPE and PET on the asphalt pavement has Marshall stability and Marshall flow values in the usable range as specified in the specification criteria of the Standard Specification for Road and Bridge Works (SSRBW). Both 8% and 10% PET perform better than same percentage of LDPE.